(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Chronic Suppurative Otitis Media (CSOM) is a commonly encountered disease among the population of developing countries like, Bangladesh. It is prevalent among people with low socio-economic status, over gathered families, recurrent upper respiratory tract infections, poor hygiene, etc. This study aimed at determining the prevalence and pattern of CSOM in population of Chattogram. Materials and methods: A descriptive cross sectional study was carried out from September 2023 to February 2024 at the outdoor department of Otorhinolaryngology of BGC Trust Medical college Hospital and Society for Assistance to Hearing Impaired Children (SAHIC) Chattogram. Results: Among 400 patients with Otitis Media 239 had CSOM. 155(64.85%) were female and 84(35.14%) were male. Patients with age ranging from 0-10 years, 63 (26.35%) were prevalent. 138(57.74%) patients with poor socioeconomic status and overcrowded families were frequently attacked with CSOM. 141(59.0%) had habit of bathing in pond. 100(41.84%) used cotton buds and 100(41.84%) used feathers, vegetable sticks and wooden sticks to clean their ears. 214(89.53%) had Tubo-tympanic variety and 25(10.46%) had Attico-antral variety of CSOM. 215(89.95%) had discharge with CSOM. Conclusion: CSOM affects adults as well as children. Neglect towards its treatment can hamper daily activities, with a poor quality of life, followed by extra-cranial or intra-cranial manifestations. JCMCTA 2024 ; 35 (1) : 120-126